Synergetic effect of cationic starch (ether/ester) and Pluronics for improving inkjet printing quality of office papers - Sharma, Mohit (2021)
Improving the printability of paper is still a relevant challenge, despite the fast development of digital communications. While it is well-known that cationic starches enhance ink density, their commercial paper-grade forms are limited to ethers with low degree of substitution. This work addresses the underexplored potential of highly substituted cationic starch for paper coating and its combination with tri-block polymers, namely Pluronics (P123 and F127), taking advantage of their supramolecular interactions with amylose chains. For that purpose, cationic starch ether and ester (starch betainate), both with a degree of substitution of 0.3, were synthesized by alkaline etherification and by transesterification, respectively. Paper without any surface treatment was subjected to one-side bar coating with suspensions encompassing those products and Pluronics, besides other common components. Black, cyan, yellow and magenta inks were printed on all coated papers through an inkjet printer. Key properties of printing quality such as the gamut area, gamut volume, optical density, print-through, inter-color bleed and circularity were measured in a controlled temperature-humidity environment. For instance, a formulation with cationic starch (ether/ester) and P123 improved the gamut area by 16–18% in comparison to native starch-coated paper sheets. Interestingly, the individual assessment of each component showed that cationic starch ether, starch betainate and P123 only improved the gamut area by 5.6%, 8.9% and 6.8%, respectively. Finally, but not less importantly, starch betainate was found to quench optical brightening agents to a lesser extent than cationic starch ethers.